2012
DOI: 10.1159/000336001
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Focused Ultrasound to the Thalamus Is Associated with Reduced Extracellular GABA Levels in Rats

Abstract: Objective: Transcranial focused ultrasound (FUS), with its ability to non-invasively modulate the excitability of region-specific brain areas, is gaining attention as a potential neurotherapeutic modality. The aim of this study was to examine whether or not FUS administered to the brain could alter the extracellular levels of glutamate and γ-aminobutyric acid (GABA), which are representative excitatory and inhibitory amino acid neurotransmitters, respectively. Methods: FUS, delivered in the form of a train of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 81 publications
2
55
0
Order By: Relevance
“…For example, the FUS-mediated functional modulation of a specific brain area may also be used as a new method for non-invasive functional brain mapping. Based on the evidence of its ability to alter the extracellular level of neurotransmitters in the rodent model2324, FUS may shed light on providing new modes of neurotherapeutics for the treatment of neurotransmitter-mediated psychiatric disorders. Furthermore, when combined conjunctively with FUS functional neurosurgery techniques1920, the presented method may be used to evaluate the function of the targeted surgical area prior to its thermal ablation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the FUS-mediated functional modulation of a specific brain area may also be used as a new method for non-invasive functional brain mapping. Based on the evidence of its ability to alter the extracellular level of neurotransmitters in the rodent model2324, FUS may shed light on providing new modes of neurotherapeutics for the treatment of neurotransmitter-mediated psychiatric disorders. Furthermore, when combined conjunctively with FUS functional neurosurgery techniques1920, the presented method may be used to evaluate the function of the targeted surgical area prior to its thermal ablation.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to reversibly modulate region-specific excitability of the sonicated brain tissue has been demonstrated by the excitation or suppression of neural activity via sonication of the motor and visual areas in rabbits21, the suppression of chemically-induced epilepsy22, and the alteration of extracellular concentrations of neurotransmitters in rats2324. In non-human primates, FUS given to the frontal eye field of macaques modulated their visuomotor behavior25.…”
mentioning
confidence: 99%
“…When administered in bursts of short pulses, FUS has been shown to reversibly excite or suppress the region-specific brain functions in rabbits 8 and rodents 9. In addition, the administration of this neuromodulatory FUS to the thalamic area of the rodent brain altered the level of extracellular neurotransmitters (γ-aminobutyric acid, dopamine, and serotonin) 10,11 and shortened the emergence time from anesthesia 12. Recently, the stimulation of rodent cranial nerves yielded the potential use of FUS in the functional modulation of the peripheral nervous system 13.…”
Section: Introductionmentioning
confidence: 99%
“…We have also recently demonstrated that FUS, when applied in short bursts of pulses, modulates neural tissue excitability in the motor and visual cortices of rabbits without changing tissue temperature (Yoo et al 2011). This exciting feature has also been applied to decrease the electrographic seizure activites from chemically-induced epileptic rats (Min et al 2011a), and to modify the extracelluar level of neurotransmitters (Min et al 2011b; Yang et al 2012). Converging evidences from these studies indicate that application of FUS at low acoustic intensity, typically under the FDA-limit for diagnostic imaging (720 mW/cm 2 I spta ; spatial-peak temporal-average intensity) (AIUM Clinical Standards Committee 2004), temporarily and reversibly modified neural function in vivo .…”
Section: Introductionmentioning
confidence: 99%